Investigation of Sensitivity of Aluminum Foil Based Strain Sensors at Fatigue Damage Evaluation of CFRP; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Burkov M. V. Mikhail Vladimirovich; Panin S. V. Sergey Viktorovich; Lyubutin P. S. Pavel Stepanovich; Eremin A. V. Alexandr Vyacheslavovich (Sensors, Measurements and Non-Destructive Control, 2014)
Title screen